Unusual Methylobacterium fujisawaense Infection in a Patient with Acute Leukaemia Undergoing Hematopoietic Stem Cell Transplantation: First Case Report - Rosa Fanci; Giampaolo Corti; Alessandro Bartoloni; Enrico Tortoli; Alessandro Mariottini; Patrizia Pecile (Case Reports in Medicine)
Microorganisms of the genus Methylobacterium are facultative methylotrophic, gram-negative rods that are ubiquitous in nature and rarely cause human disease, mostly in subjects with preexisting causes of immune depression. Methylobacterium fujisawaense, first proposed as a new species in 1988, has never been reported as a bacterial agent of human infections so far. Here we describe a case of M. fujisawaense infection in a relapsed acute leukaemia undergoing unrelated allogeneic hematopoietic stem cell transplantation. Molecular identification of an M. fujisawaense strain was obtained from multiple mycobacterial blood cultures.